1985
DOI: 10.1016/0041-008x(85)90266-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of high density lipoproteins in the biodistribution of two radioiodinated probes in the rat

Abstract: Two radioiodinated probes, '%cholesteryl oleate ('251-CO), a derivative of a natural constituent of lipoproteins, and l-(2-chlorophenyl)-1-(4['25I]iodopheny1>2,2-dichloroethane ('%DDD), an analog of the adrenolytic drug o,p'-DDD (mitotane), were selected to study the role of lipoproteins in drug disposition and to examine the ability of these vehicles to direct foreign molecules to specific tissues. In vivo and in vitro techniques were utilized to associate these probes with rat high density lipoproteins (HDL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…However, such mechanisms remain to be elucidated. For instance, mitotane is bound to lipoproteins in the plasma (30,31) and access to target tissue such as the brain is dependent on lipoprotein profiles (32). Furthermore, mitotane has been shown to affect lipoprotein profiles by increasing low-density lipoprotein and high-density lipoproteins (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, such mechanisms remain to be elucidated. For instance, mitotane is bound to lipoproteins in the plasma (30,31) and access to target tissue such as the brain is dependent on lipoprotein profiles (32). Furthermore, mitotane has been shown to affect lipoprotein profiles by increasing low-density lipoprotein and high-density lipoproteins (28).…”
Section: Discussionmentioning
confidence: 99%
“…39) Administration of 4-APP to rats has been reported to induce a marked depletion of cholesterol from the adrenal glands, upregulation of low-density lipoprotein receptors on adrenal cell membranes, [40][41][42] and high plasma adrenocorticotropic hormone (ACTH) levels. 43,44) The rat adrenal uptake of potential adrenal imaging agents such as radioiodinated cholesteryl esters 42,45) and cholesteryl-p-[ 18 F]fluorobenzoate, 35) has been shown to increase when pretreated with 4-APP. Although the function of AsA in the adrenal gland is incompletely understood, the participation of AsA in steroidogenesis has been suggested for a long time.…”
Section: Chemistry and Radiochemistrymentioning
confidence: 99%
“…Factors of primary importance are related to the structure of the lipoprotein fraction (the surface apoproteins and the lipid composition of the lipid core), the abundance of each of the individual lipoprotein fractions in plasma, as well as the type of xenobiotic and its lipophilicity (see also Vomachka et al 1984;Busbee et al 1985;Pohland and Counsell 1985).…”
Section: Discussionmentioning
confidence: 98%
“…The results of earlier investigations support the view that the binding is of a non-specific nature closely related to the lipophilicity of the compound. Recent studies, however, have indicated that the preference of a lipophilic compound for lipoproteins cannot be explained entirely on the basis of lipid solubility (Vomachka et al 1984;Pohland and Counsell 1985). The associations between xenobiotics and lipoproteins give rise to questions about possible effects of lipoproteins on the tissue uptake of these types of lipophilic compounds, and conversely, the effect of xenobiotics on the metabolism of lipoproteins.…”
Section: Offprint Requests To: a Mohammedmentioning
confidence: 96%